Reflecciones sobre el trabajo de James Heckman - Ward-Batts, Jennifer (2000)
Over the past 2-3 decades, [the recently nominated Nobel laureate in economics], James Heckman, has made significant contributions to the econometric literature, primarily related to the evaluation, measurement, and impacts of social programs. Much of his work has highlighted the problem of bias in selection bias. This is an important aspect for many empirical investigations, particularly those related to the evaluation of social programs. For this reason, we have seen the usefulness of having a set of guides that allow us to carry out the process of identifying the selection models; concept that has been given little treatment in the econometric literature.